UNVERRICHT LUNDBORG DISEASE ASSOCIATED WITH SENSORINEURAL DEAFNESS IN A PATIENT OF INDIAN ORIGIN. Issue 11 (9th October 2013) - Akhtar, Nadeem; Omer, Salah
Abstract : Unverricht Lundborg (ULD) disease is the commonest cause of the progressive myoclonus epilepsy. It is caused by mutations in the gene encoding the enzyme Cystatin B, a cystine protease inhibitor. The condition has rarely been reported outside the Baltic and Mediterranean regions. We report a case of ULD in association with sensory neural deafness in a patient of Indian origin. A 45 year old male patient was referred to us because of limb jerking, loss of balance and generalised seizures since he was 12 years old. His symptoms have progressed slowly over the years. The jerking was most severe in the morning, in crowded noisy environments, and when exposed to bright lights. He developed sensory neural deafness in the first decade of life. The patient was the product of a consanguineous marriage. A sister of his developed similar symptoms at the same age and died during a generalised seizure in her early 40s. Four maternal cousins have very similar symptoms. Examination revealed multifocal myoclonus in his limbs and face, cerebellar ataxia and mild cognitive impairment. Brain MRI scan and EEG were normal and a 48–hour video telemetry did not reveal any abnormality even though he had frequent myoclonic jerks during the recording. Muscle biopsy and molecular tests excluded a mitochondrial disorder. He was confirmed to be homozygous for the pathological repeat expansion associated with ULD. To our knowledge this is the first genetically confirmed case of ULD in a patient of Indian origin. Sensorineural deafness in association with ULD has only been reported once in a Serbian family. This case highlights the importance of considering the diagnosis of ULD in any patient presenting with stimulus sensitive myoclonus, generalised seizures, and ataxia irrespective of their ethnic origin or EEG findings.